AN AI APPROACH TO ANALYZING AND ENHANCING EMPLOYEE WELLBEING AND PRODUCTIVITY - Jovanovic, Sonja; Petrović, Aleksandar; Dražeta, Lazar (The European Journal of Applied Economics, 2025)
This paper explores the complex concept of wellbeing, emphasizing its significance in both personal and professional contexts. Wellbeing encompasses physical, mental, emotional, social, spiritual, financial, career, occupational, intellectual, digital, and environmental dimensions. The COVID-19 pandemic has heightened awareness of mental and physical wellbeing, prompting organizations to prioritize these aspects. Effective wellbeing strategies enhance productivity, resilience, and overall organizational success. Remote work, a growing trend, offers flexibility and improved work-life balance but also presents challenges such as isolation and blurred boundaries. By understanding the evolution of remote work and implementing strategies to support employee wellbeing, organizations can foster a harmonious and productive work environment. Artificial intelligence is becoming instrumental for increasing employee performance and this work explores such approaches for better understanding and prediction of work trends. This paper underscores the importance of personalized wellbeing approaches, recognizing that individual needs vary, and generic solutions may not suffice. Ultimately, prioritizing wellbeing leads to sustainable personal and professional growth.